Development of Problem-Based Senior High School Mathematics Learning Tools with a Culturally Responsive Teaching Approach - Fathani, Abdul Halim; Ismi Nurafdila Pangestu (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2024)
This development research aims to produce valid, practical, and effective senior high school mathematics learning tools through problem-based learning with a Culturally Responsive Teaching approach. The research employed a 4-D model, consisting of the Define, Design, Develop, and Disseminate stages. The research subjects were 36 students in Class X-4 of SMAN 3 Lumajang for the 2022/2023 academic year. The learning tools outcomes included teaching modules, students’ worksheets (LKPD), student activity observation sheets, and test questions. The established criteria revealed that the learning tools outcomes were valid, effective, and practical. Hopefully, further research could develop more varied learning tools regarding materials, learning models, and integrated culture.